Study of legume-rhizobia symbiosis in soybean for agroecosystem resilience - Oleksandr Mazur; Olena Mazur; Tetiana Tymoshchuk; Ihor Didur; Viacheslav Tsyhanskyi (Наукові горизонти)
Research into innovative methods of regulating legume-rhizobia symbiosis is crucial for enhancing nitrogen fixation, thereby promoting soil health and increasing crop yields. This contributes to sustainable agriculture by reducing the need for chemical fertilisers and enhancing the resilience of agroecosystems. The study aimed to determine the impact of seed inoculation, environmental conditions, and varietal characteristics of soybean varieties on biological nitrogen accumulation. The research was conducted under the environmental conditions of Kyiv, Poltava, and Vinnytsia regions from 2010 to 2021. Cultivation practices for the soybean varieties adhered to standard regional agronomic guidelines. The findings detail the effects of seed inoculation on the dynamics of formation and productivity of soybean-rhizobial symbiosis in soils with existing native rhizobial populations. The nitrogen-fixing potential of soybean varieties under inoculation was identified, showing that inoculation enhances the efficiency of the soybean symbiotic system. It has been demonstrated that, across varied environmental conditions, seed inoculation with Bradyrhizobium japonicum enhances the formation and functioning of the soybean symbiotic apparatus, even in soils with existing native populations of nodule bacteria. The efficacy of seed inoculation is influenced by the hydrothermal conditions of the year, environmental factors, and soybean variety. Seed inoculation contributes to the development of a greater mass of active nodules on plant roots, positively impacting nitrogen fixation. The highest nitrogen fixation levels were observed in the soybean varieties Ametyst, Artemida, and Hoverla across different environmental conditions. Seed inoculation increased the amount of biologically fixed nitrogen in these varieties by 33.9-36.1 kg/ha. Varieties Ametyst, Artemida, and Hoverla showed a particularly strong response to inoculation with nitrogenfixing bacteria and are recommended for cultivation in diverse environmental conditions. Innovative approaches to enhancing the efficiency of the soybean legume-rhizobia symbiosis through the use of biological inoculants based on nitrogen-fixing bacteria will enable the development of biologically-oriented cultivation technologies, promoting the resilience of agroecosystems